(untitled) (Medico Legal Update, 2020)
Health information systems play a role in providing data, information and health indicators to support the management process will have an impact on increasing the effectiveness of work. The purpose of this research is to know the quality influence of health information system that is seen from availability, timeliness, and relevance to the effectiveness of employees of public health centers in Ambon City. The type of research used is quantitative with cross sectional study design. The population in this study is all employees of the Ambon City Public Health Center amounting to 586 people, the withdrawal of samples with purposive technique obtained by 50 people. Collection of data through questionnaires. Data is analyzed by chi-square test. The results showed that the health information system of the availability aspect (P = 0.02), timely (P = 0.01) and relevant (P = 0.04) significantly affected the effectiveness of healthcare personnel working in the Public health center in Ambon city. It is hoped that the public health center in Ambon City can improve the existing system so that the information produced is more quality.